Lugares da memória: a vivência da migração nordestina no interior paulista entre avós e netos - Silva, Cinthia Xavier da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the mid 20th century an expressive internal migration took place in Brazil, mostly from the Northeast of the country to the industrial capitals of the Southeast, but also to small new towns in the State of São Paulo. We examine here the narratives of this important but often overlooked migration as they are told by the migrating families that settled in Barbosa, a city that sprang from a late 19th century settlement located 300 miles from the cap ital. Through extensive field research and interviews with “Nordestinos” who migrated in the 1930s, 40s and 50s, their children and grandchildren, including the family of the researcher herself, we examine how migration narratives are transmitted between generations in what we are calling “places of memory”: situations created by the migrating grandparents or inherited from Northeastern traditions in which the past in the place of origin is remembered, the migration itself is recalled and, above all, a certain way of being and acting is taught to the younger generation. Among the places of memory we identified are family gatherings around life cycle events; public gatherings where fathers and grandfathers publicly tell stories about characters collectively known; domestic spaces where mothers and grandmothers make sense of the family history; religious festivities such as “Festas Juninas” and “Terços” taking place in June and July; the fantastic realm of stories where mystic beings and animals relate to human beings; and, last but not least, the forms of media that supported memories and narratives in this strongly oral culture (such as photographs and wall portraits kept during the migration or sent back and forth by mail to relatives in the Northeast). In spite of the important role migration narratives and their attached teachings have for this community, we noticed that they and their context are largely absent from public school de facto curriculum. Basic education...

Esta pesquisa tem como objetivo entender como a memória da migração nordestina para o interior do estado de São Paulo existe nas famílias destes migrantes. Ou seja, como as histórias da migração são transmitidas entre avós e netos. Investigamos o contexto em que esta migração ocorreu, entre 1930 e 1960, em uma cidade do interior de São Paulo, Barbosa, localizada no noroeste do estado, cujo povoamento data de final do século XIX. Através de pesquisa qualitativa, com inserção no campo pesquisado e entrevistas com avós migrantes e seus netos, além de entrevistas com três filhas de migrantes e da recuperação da experiência familiar da própria pesquisadora, observamos que as histórias da migração são transmitidas no que chamamos de “lugares da memória”. Tratam- se de lugares criados pelos avós migrantes ou herdados pela tradição para reviver o passado no lugar de origem, relembrar a migração e ensinar as futuras gerações um modo de ser e agir dentro deste grupo. Estes lugares da memória se constituem quando se abrem portas para que a memória surja: são as festas de família; os locais públicos onde pais e avós contam histórias e os espaços domésticos onde as mães e avós relatam histórias de família; as malas com fotografias guardadas durante a migração ou trocadas posteriormente em cartas, assim como os retratos de parede; as festas juninas e os terços que acontecem durante os meses de junho e julho; e o universo fantástico com narrativas compostas pelo relacionamento entre seres místicos ou animais que se relacionam com humanos. As narrativas são muito importantes para este grupo pesquisado, pois ensinam como proceder corretamente através de conselhos, relatos de experiências. Descobrimos também que a migração nordestina para o interior de São Paulo não é contada na educação básica, onde se dá ênfase à migração de nordestinos para a capital de São Paulo e à migração...
Keywords: Migração interna; Historia oral; Migration, Internal; Brasil, Nordeste; São Paulo (Estado)